Prey consumption and development of the indigenous lacewing Chrysoperla externa feeding on two exotic Eucalyptus pests - Cuello, Eliana Marina; Andorno, Andrea Veronica; Hernandez, Carmen Marcela; Lopez, Silvia Noemi (Taylor & Francis, 2020)
The green lacewing Chrysoperla externa is a widespread species in the Neotropical region that occurs in different habitats. Its presence in Eucalyptus plantations infested with Glycaspis brimblecombei (Hemiptera: Aphalaridae) and Thaumastocoris peregrinus (Hemiptera: Thaumastocoridae) suggests that this lacewing might feed on one or both exotic pest species. In order to evaluate C. externa as a potential biocontrol agent of the eucalyptus pests, the prey consumption, development, survival and reproduction of the predator were evaluated under laboratory conditions. C. externa larvae consumed nymphs of both pest species. Developmental time and reproduction parameters of C. externa fed G. brimblecombei were similar to those obtained with the factitious prey Sitotroga cerealella. When fed on T. peregrinus, C. externa showed a delay in its developmental time and the emerged adults were malformed. The results of this study suggest that the green lacewing is a good candidate to be used in augmentative or conservative biological control programmes against G. brimblecombei. Further research is necessary to analyse the potential of this predator as a biocontrol agent under field conditions.